Snap beans: Present status in the developing world and bibliography of research (1919-1987) - Janssen, W.; López S, J.; González V, F (International Center for Tropical Agriculture, 1988)
The present status of snap beans in the developing world is reviewed in the leading paper accompanying this publication. Socioeconomic aspects are mainly discussed. Production, marketing, and consumption features are described and the future potential for the crop is outlined. Constraints to production increases are discussed and the opportunities for research and development of the crop are defined. The bibliography contains 922 references to research on snap beans. Most of the documents (761) are available at CIAT. References are organized by disciplines and are complemented with author and subject indexes. The institutions identified by the Bean Information Center as carrying out research on snap beans are listed in the enclosed preliminary directory, which also includes the names of the snap bean researchers recorded in the CIAT database and the participants in the workshop on snap bean breeding held at CIAT in 1987. (CIAT)